IL-33 down-regulates CLDN1 expression through the ERK/STAT3 pathway in keratinocytes. Issue 3 (June 2018) - Ryu, Woo-In; Lee, Hana; Bae, Hyun Cheol; Jeon, Jiehyun; Ryu, Hwa Jung; Kim, Jaehyung; Kim, Ji Hyun; Son, Ji Won; Kim, JaeYoung; Imai, Yasutomo; Yamanishi, Kiyofumi; Jeong, Sang Hoon; et al.
Highlights: IL-33 may be key regulator of CLDN1 downregulation in keratinocytes. The expression of CLDN1 is regulated by ERK/STAT3 pathway in IL-33 treated keratinocytes. IL-33 reduced CLDN1 expression is regulated by direct binding of STAT3 to CLDN1 promoter region. Abstract: Background: Tight junctions (TJs) have important roles in skin barrier function. The TJ protein claudin-1 (CLDN1) is decreased in atopic dermatitis (AD). However, little is known about the mechanism of CLDN1 down-expression. Objective: To elucidate the effect of IL-33 on CLDN1 expression in keratinocytes. Methods: Normal human epidermal keratinocytes (NHEKs) and human skin equivalent models (HSEMs) were cultured in vitro in the presence of IL-33. Production of CLDN1, signal transducer and activator of transcription 3 (STAT3) and Mitogen-activated protein kinases (MAPK) expression were measured by real-time PCR, western blot and immunofluorescence assay. MAPK inhibitors and small interfering RNA were used to confirm the signal pathway of STAT3 and CLDN1. Barrier function was measured by transepithelial electric resistance (TEER) and FITC-dextran flux assays. Electrophoretic Mobility Shift Assay was used to detect STAT3 transcriptional activity. Results: Levels of CLDN1 expression were reduced in the epidermis of AD-model mice overexpressing IL-33. IL-33 down-regulated the expression of CLDN1 mRNA and protein in NHEKs and HSEMs. IL-33 attenuated transepithelial electric resistance and induced FITC-dextran flux in NHEKs. The IL-33 suppressed CLDN1 expression was regulated by an extracellular signal-regulated kinase (ERK) and signal transducer and activator of transcription 3 (STAT3). STAT3 suppressed CLDN1 expression by direct binding to the promoters. Conclusion: IL-33 may down-regulate CLDN1 expression through the ERK/STAT3 pathway in keratinocytes.